Transformaciones en los atributos valorados. Flexibilización laboral, competencias laborales y desplazamiento del actor sindical en Argentina - Álvarez Newman, Diego (2019)
The purpose of this article is to address the transformations in the valued attributes of workers, through the analysis of policies based on labor competencies.The hypothesis is that the competences paradigm facilitates the implementation of individualized work management models, in which soft skills take relevance. These management modalities displace unions from participating in the definition of valued attributes. We will use a qualitative methodology. The data sources were documents from national and international organizations in charge of implementing labor competencies policies in Argentina, and collective labor agreements in the automotive sector. In addition, in-depth interviews were used with workers and group leaders from a Japanese automotive terminal.